THE FIGURE OF SHAMAN AS THE POTENTIAL MODEL OF LEADER IN MUSIC AND MUSICAL EDUCATION - Bałajewicz, Magda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Shaman is an individual, gifted with plenty of unusual skills - the medium between two worlds, human and the external one. Being a leader and healer, shaman is master for the younger entrants, leading them through the difficult initiation process and preparing them to independent work on their potential in the future. With time shamanism became a sort of the cultural model associated with pop-culture: a path of the artistic and spiritual transformation, a form of opposition for excluded communities, a type of common experience of art and a prototype of the figure of leader. The consciousness of the existence of this kind of artistic and psychological model and the possibility of its use in art could be the key element in young artist's music educational process, based on the intimate relation between the student and the master, especially in jazz music genre. In this context extremely important is informal and non-formal education - lasting for the whole life, it allows the artist to develop their individual personality and sensitivity on every level of existence. In this perspective the figure of shaman - first entrant, later leader - could be a valuable and useful educational model.